Motivational dynamics of German Salafist jihadists: A multi-methodical in-depth study of three paradigmatic cases - Moeller, Mika Josephine; Langer, Phil C.; Scheithauer, Herbert (Frontiers in Psychology, 2022)
Individuals belonging to terrorist organizations – such as Salafist jihadists ones – accept and often use violence as an instrument of their strategies to achieve their goals. The present study focuses on the motivational dynamics of three contrastively selected paradigmatic cases of extremists that grew up in Germany, joined and supported terrorist organizations abroad, later disengaged and distanced themselves from the jihadist ideology. An innovative multi-methodical approach was applied to the interviews that combines a biographical reconstruction of the lived experiences with a psychoanalytically informed interpretation of the narratives. First, the biographical trajectories were analyzed on the manifest level: How have the former terrorists experienced their own pathways? What were relevant factors for their engagement in and disengagement from terrorism? Second, to gain a deeper understanding of the unconscious motivational dynamics for involvement in terrorism, key sequences of the narrative interviews were interpreted scenically in a psychoanalytically working interpretation group: How did the interviewees express their lived experiences (and why in this particular way)? What latent meanings can be extrapolated that provide deep insights into the motivational backgrounds of their decisions? Based on the results of the triangulation process, characterizing structural hypotheses about case dynamics including protective and risk factors are presented and implications for approaches for prevention and intervention are given.